2013
DOI: 10.1007/s00264-013-2089-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a central zone in scaphoid surgery: a computational approach

Abstract: Purpose Scaphoid fractures are commonly fixed with headless cannulated screws positioned centrally in the scaphoid. Judgement of central placement of the screw may be difficult. We generated a central zone using computer analysis of 3D reconstructions of computed tomography (CT) images. As long as the screw axis is completely contained within this central zone, the screw would be considered as centrally placed. Methods Thirty cases of 3D CT reconstructions of normal scaphoids in a computerised operation planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…17 Guo et al in 2014 showed that the central zones of the three scaphoid segments (proximal, waist and distal) are not continuous due to the irregular anatomy of the scaphoid bone and that it might not be possible to insert a screw that passes through the central zones of all three segments. 18 Quan et al in 2017 acknowledged the possibility of iatrogenic perforation of the scaphoid cortex especially if the screws appear close to the scaphoid cortex. 7 We are not aware of any publications describing the thickness of the articular cartilage surrounding the scaphoid.…”
Section: Discussionmentioning
confidence: 99%
“…17 Guo et al in 2014 showed that the central zones of the three scaphoid segments (proximal, waist and distal) are not continuous due to the irregular anatomy of the scaphoid bone and that it might not be possible to insert a screw that passes through the central zones of all three segments. 18 Quan et al in 2017 acknowledged the possibility of iatrogenic perforation of the scaphoid cortex especially if the screws appear close to the scaphoid cortex. 7 We are not aware of any publications describing the thickness of the articular cartilage surrounding the scaphoid.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,9 However, due to variations in scaphoid anatomy and fracture morphology, central third placement may not be ideal in all patients. 26 Our software allows the surgeon to make adjustments to ensure the screw is contained entirely within the scaphoid bone. Thus, preprocedure planning for the targeting device group was aimed at maximizing K-wire length within the scaphoid, but this came at the expense of some K-wire trajectories traveling outside the central axis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, preprocedure planning for the targeting device group was aimed at maximizing K-wire length within the scaphoid, but this came at the expense of some K-wire trajectories traveling outside the central axis. Guo et al 26 examined 30 scaphoid CT reconstructions and determined that the central zone could be defined within the proximal, waist, or distal portions of the scaphoid, but a single screw could rarely be inserted through the central zone of all three portions concurrently. Still, we reported the number of K-wires placed within the central third to allow comparison of accuracy between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…1). As there is no clear definition of the scaphoid center due to the curved, irregular geometry [16], we calculated the centroids of the proximal and distal poles in transverse cross-sections at 25% and 75% length and defined the scaphoid center as the point halfway these centroids.…”
Section: Screw Placement Simulationmentioning
confidence: 99%